Análisis de la información científica de la sostenibilidad ambiental y su incidencia en el bosque húmedo de la zona noroccidental de la provincia de Cotopaxi. - Chiluisa Checa, Kelly Pamela (2021)
This research allowed me to know the current state of the northwestern forest of Cotopaxi Province, identifying tree species, number of crops and introduced animal species, as well as determining the main anthropogenic factors that affect that place, and the incidence of the temperature and precipitation in this area of study in order to ensure of the natural resources sustainability. Therefore, the research topic was proposed as follows "Analysis of scientific information on environmental sustainability and its impact on the humid forest in the northwestern area of Cotopaxi Province". The specific objectives were: to systematize the existing information on environmental sustainability in the humid forest, to examine the bases of scientific and bibliographic Journals about the topics during the period 2015 - 2020, and to propose the conservation of the humid forest in the northwestern area of the province. In relation to the systematization of information, the current situation of the forest was analyzed from conceptualizations and data established in research carried out in this area. Furthermore, it was establised the type of affectation that the rainforest has suffered and how it has affected the conditions of the environmental sustainability in this area. With the results obtained from the analysis of the information, a conservation proposal for the study area was established, with the purpose of guaranteeing the maintenance and recovery of those areas that are affected by the biotic and abiotic factors of the rainforest.